Prolactin increases expression of cytoskeletal proteins in SK-N-SH cells - Havránek, T; Bačová, Z; Štrbák, Vladimír; Lešťanová, Z; Bakoš, Ján (Folia biologica (Praha), 2014)
Although many studies have demonstrated the role of prolactin in the central nervous system, there is a considerable lack of known effects of prolactin on the parameters of neurogenesis and neuronal differentiation. The aim of the present study was to test whether prolactin changes gene expression and protein levels of nestin and microtubule-associated protein 2 (MAP2) in neuroblastoma (SK-N-SH) and glioblastoma (U-87MG) cells. Nestin and MAP2 represent cytoskeletal proteins associated with neuronal differentiation and they contribute to radial growth of the axons, dendrites and glial processes. SK-N-SH and U-87MG cells were exposed to prolactin (10 nM) for 48 h. Total mRNA was extracted. After reverse transcription, qPCR with specific primers for nestin and MAP2 was performed. The levels of proteins were measured by the In-Cell Western assay. Mitochondrial activity test was used to evaluate the viability of cells under the influence of prolactin. Incubation with 10 nM prolactin did not change the viability, either in SK-N-SH or in U-87MG cells. Prolactin significantly increased the gene expression and protein levels of both nestin and MAP2 in SK-N-SH cells, while no significant changes were observed in U-87MG cells. The presented data suggest that prolactin is linked to the regulation of cytoskeletal proteins in the neuronal type of cells and might be important for their differentiation.
Keywords: glioblastom; nádorové proteiny; Gene Expression Regulation, Neoplastic; Microtubule-Associated Proteins; Recombinant Proteins; Up-Regulation; Cell Line, Tumor; Organ Specificity; Cytoskeletal Proteins; regulace genové exprese u nádorů; Nestin; upregulace; proteiny asociované s mikrotubuly; cytoskeletální proteiny; prolaktin; neurony; Neuroblastoma; rekombinantní proteiny; lidé; neuroblastom; Prolactin; Humans; Neurons; neuroglie; Neoplasm Proteins; Neuroglia; neurogeneze; nádorové buněčné linie; orgánová specificita; Glioblastoma; nestin; Neurogenesis